Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Join our platform to connect with experts ready to provide accurate answers to your questions in various fields. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Sure! Let's graph the function [tex]\( h(x)=6 \cdot\left(\frac{4}{3}\right)^x \)[/tex] step-by-step.
### Step 1: Understanding the function
The given function is an exponential function. The base of the exponential term is greater than 1, which means the function will show exponential growth.
- The base of the exponent is [tex]\( \frac{4}{3} \)[/tex].
- The coefficient 6 controls the initial value when [tex]\( x=0 \)[/tex].
### Step 2: Creating a table of values
To graph the function, we can start by calculating some values of [tex]\( h(x) \)[/tex] for selected [tex]\( x \)[/tex] values.
| [tex]\( x \)[/tex] | [tex]\( h(x) = 6 \cdot \left( \frac{4}{3}\right)^x \)[/tex] |
|------|-------------------------------------------|
| -3 | [tex]\( 6 \cdot \left( \frac{4}{3} \right)^{-3} = 6 \cdot \left( \frac{3}{4} \right)^3 = 6 \cdot \frac{27}{64} \approx 2.53 \)[/tex] |
| -2 | [tex]\( 6 \cdot \left( \frac{4}{3} \right)^{-2} = 6 \cdot \left( \frac{3}{4} \right)^2 = 6 \cdot \frac{9}{16} = 6 \cdot 0.5625 = 3.375 \)[/tex] |
| -1 | [tex]\( 6 \cdot \left( \frac{4}{3} \right)^{-1} = 6 \cdot \left( \frac{3}{4} \right) = 6 \cdot 0.75 = 4.5 \)[/tex] |
| 0 | [tex]\( 6 \cdot 1 = 6 \)[/tex] |
| 1 | [tex]\( 6 \cdot \left( \frac{4}{3} \right) = 6 \cdot 1.333 = 8 \)[/tex] |
| 2 | [tex]\( 6 \cdot \left( \frac{4}{3} \right)^2 = 6 \cdot 1.777 = 10.67 \)[/tex] |
| 3 | [tex]\( 6 \cdot \left( \frac{4}{3} \right)^3 = 6 \cdot 2.37 = 14.22 \)[/tex] |
### Step 3: Plotting the points
We will now plot these points on a Cartesian plane:
- At [tex]\( x = -3 \)[/tex], [tex]\( h(x) \approx 2.53 \)[/tex]
- At [tex]\( x = -2 \)[/tex], [tex]\( h(x) = 3.375 \)[/tex]
- At [tex]\( x = -1 \)[/tex], [tex]\( h(x) = 4.5 \)[/tex]
- At [tex]\( x = 0 \)[/tex], [tex]\( h(x) = 6 \)[/tex]
- At [tex]\( x = 1 \)[/tex], [tex]\( h(x) = 8 \)[/tex]
- At [tex]\( x = 2 \)[/tex], [tex]\( h(x) = 10.67 \)[/tex]
- At [tex]\( x = 3 \)[/tex], [tex]\( h(x) = 14.22 \)[/tex]
### Step 4: Drawing the graph
1. Draw the horizontal axis (x-axis) and the vertical axis (y-axis).
2. Label the axes with appropriate scales. Since the y-values grow exponentially, we may need a larger range for the y-axis.
3. Plot the points calculated above on the graph.
4. Finally, draw a smooth curve through the points to represent the exponential function.
### Visual Representation
Here is how you might envision the plot:
- The graph will pass through the points mentioned, showing an exponential rise as [tex]\( x \)[/tex] increases.
- For [tex]\( x < 0 \)[/tex], the function values will get closer and closer to zero but remain positive (since the exponential function never touches the x-axis).
### Additional Points
- The y-intercept is at (0, 6) since [tex]\( h(0) = 6 \)[/tex].
- The graph will asymptote towards the x-axis but never touch or cross it.
By joining these points with a smooth curve, you will obtain the graph of the function [tex]\( h(x) = 6 \cdot \left( \frac{4}{3} \right)^x \)[/tex]. As [tex]\( x \)[/tex] becomes more positive, [tex]\( h(x) \)[/tex] increases rapidly, illustrating the nature of exponential growth.
### Step 1: Understanding the function
The given function is an exponential function. The base of the exponential term is greater than 1, which means the function will show exponential growth.
- The base of the exponent is [tex]\( \frac{4}{3} \)[/tex].
- The coefficient 6 controls the initial value when [tex]\( x=0 \)[/tex].
### Step 2: Creating a table of values
To graph the function, we can start by calculating some values of [tex]\( h(x) \)[/tex] for selected [tex]\( x \)[/tex] values.
| [tex]\( x \)[/tex] | [tex]\( h(x) = 6 \cdot \left( \frac{4}{3}\right)^x \)[/tex] |
|------|-------------------------------------------|
| -3 | [tex]\( 6 \cdot \left( \frac{4}{3} \right)^{-3} = 6 \cdot \left( \frac{3}{4} \right)^3 = 6 \cdot \frac{27}{64} \approx 2.53 \)[/tex] |
| -2 | [tex]\( 6 \cdot \left( \frac{4}{3} \right)^{-2} = 6 \cdot \left( \frac{3}{4} \right)^2 = 6 \cdot \frac{9}{16} = 6 \cdot 0.5625 = 3.375 \)[/tex] |
| -1 | [tex]\( 6 \cdot \left( \frac{4}{3} \right)^{-1} = 6 \cdot \left( \frac{3}{4} \right) = 6 \cdot 0.75 = 4.5 \)[/tex] |
| 0 | [tex]\( 6 \cdot 1 = 6 \)[/tex] |
| 1 | [tex]\( 6 \cdot \left( \frac{4}{3} \right) = 6 \cdot 1.333 = 8 \)[/tex] |
| 2 | [tex]\( 6 \cdot \left( \frac{4}{3} \right)^2 = 6 \cdot 1.777 = 10.67 \)[/tex] |
| 3 | [tex]\( 6 \cdot \left( \frac{4}{3} \right)^3 = 6 \cdot 2.37 = 14.22 \)[/tex] |
### Step 3: Plotting the points
We will now plot these points on a Cartesian plane:
- At [tex]\( x = -3 \)[/tex], [tex]\( h(x) \approx 2.53 \)[/tex]
- At [tex]\( x = -2 \)[/tex], [tex]\( h(x) = 3.375 \)[/tex]
- At [tex]\( x = -1 \)[/tex], [tex]\( h(x) = 4.5 \)[/tex]
- At [tex]\( x = 0 \)[/tex], [tex]\( h(x) = 6 \)[/tex]
- At [tex]\( x = 1 \)[/tex], [tex]\( h(x) = 8 \)[/tex]
- At [tex]\( x = 2 \)[/tex], [tex]\( h(x) = 10.67 \)[/tex]
- At [tex]\( x = 3 \)[/tex], [tex]\( h(x) = 14.22 \)[/tex]
### Step 4: Drawing the graph
1. Draw the horizontal axis (x-axis) and the vertical axis (y-axis).
2. Label the axes with appropriate scales. Since the y-values grow exponentially, we may need a larger range for the y-axis.
3. Plot the points calculated above on the graph.
4. Finally, draw a smooth curve through the points to represent the exponential function.
### Visual Representation
Here is how you might envision the plot:
- The graph will pass through the points mentioned, showing an exponential rise as [tex]\( x \)[/tex] increases.
- For [tex]\( x < 0 \)[/tex], the function values will get closer and closer to zero but remain positive (since the exponential function never touches the x-axis).
### Additional Points
- The y-intercept is at (0, 6) since [tex]\( h(0) = 6 \)[/tex].
- The graph will asymptote towards the x-axis but never touch or cross it.
By joining these points with a smooth curve, you will obtain the graph of the function [tex]\( h(x) = 6 \cdot \left( \frac{4}{3} \right)^x \)[/tex]. As [tex]\( x \)[/tex] becomes more positive, [tex]\( h(x) \)[/tex] increases rapidly, illustrating the nature of exponential growth.
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.